Monitoração do ambiente externo de negócios: um estudo de caso - Adriane Maria Arantes de Carvalho (1998)
The environmental scanning process associated to the strategic planning process turns information about events and trends in the external environment available to the company, information that are necessary to elaborate strategies and to support the strategic decision making process. This study discusses the practices adopted by a bigbrazilian telecommunication company to scan the external environment. It includes subjects as the scanning scope, the information sources, the information management and the performance of the scanning activities. It also presents some proposals to structure the environmental scanning activities at this company in order to improve the performance and the efficiency of its activities.